Corporate Social Responsibility (CSR) in Indonesia: Bibliometric Analysis and Research Trends - selly, Selly Puspita Sari; Mulyono, Andi; Fuadi, Fauzan (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Scientific research on Corporate Social Responsibility (CSR) has increased rapidly over the last few decades. This study aims to comprehend CSR's current state and implementation in Indonesia. We conducted a bibliometric analysis of the CSR study from 2006 to 2024 to identify the publication trends in this field of study. Based on the keywords associated with CSR in the article title, this study analyzed 209 documents. The bibliometric analysis of this study is based on Scopus database information. Excel was employed for frequency analysis. This study analyzes the publication year, document type, source, title, field of study, authorship, and citation analysis to convey its findings.